2018
DOI: 10.18203/issn.2454-2156.intjscirep20182083
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress/PERK/apoptotic pathways interaction contribute to tramadol neurotoxicity in rat cerebral and cerebellar cortex and thyme enhances the antioxidant defense system: histological, immunohistochemical and ultrastructural study

Abstract: <p class="abstract"><strong>Background:</strong> Tramadol is an opioid analgesic with several adverse reactions. Oxidative and endoplasmic reticulum (ER) stresses have been involved in the molecular mechanisms underlying tramadol neurotoxicity. Importantly, protein kinase RNA-like ER kinase (PERK) is a key ER-downstream pathway that mediates apoptosis. We aimed to determine the cellular stresses interaction that mediates PERK-induced apoptosis in tramadol-treated rats and to assess the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…In this study the observed dilated congested blood capillaries could be explained by the vasodilatory effect of the produced nitric oxide [35] . Abdel-Zaher et al, 2011 [36] found that tramadol administration for consecutive days increased nitric oxide levels in the brain which played a critical role in the development of the ovarian follicles, function of the corpus luteam and ovulation [37] .…”
Section: Discussionsupporting
confidence: 50%
“…In this study the observed dilated congested blood capillaries could be explained by the vasodilatory effect of the produced nitric oxide [35] . Abdel-Zaher et al, 2011 [36] found that tramadol administration for consecutive days increased nitric oxide levels in the brain which played a critical role in the development of the ovarian follicles, function of the corpus luteam and ovulation [37] .…”
Section: Discussionsupporting
confidence: 50%
“…In 2016, the National Survey on Drug Use and Health (NS-DUH) reported that 1.6 million people over the age of 12 years used Tra for non-medical reasons in the United States (2). In previous reports, a wide range of side effects has been attributed to Tra consumption, including histopathological and biochemical damage to the liver, kidneys, testis (4-6) and brain of rats (7). According to previous studies, several mechanisms are involved in Tra-induced toxicity, such as oxidative stress (5,8) and cell death (9).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental studies indicated that the chronic TR administration altered neurotransmitter levels and oxidative stress in the brain [20,[24][25][26][27]. For example, in an experimental study, chronic tramadol administration (30 or 60 mg/kg via oral gavage; for 8 weeks) revealed a significantly increased lipid peroxidation and NO, and decreased GSH level and antioxidant enzymes activity and expression in the cerebrum.…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Besides, the ultrastructural changes of mitochondria and cytoskeletal structure with the disruption of oxidative damage, apoptosis, energy metabolism, and signal transduction pathways were determined [26]. Raj et al suggested that the long-term administration of TR in rats (50 mg/kg, intraperitoneal injection for 28 days) altered oxidative stress markers (including lipid peroxidation, nitrite, GSH, Glutathione Peroxidase (GPx) activity, SOD, CAT, mitochondrial complex I, IV, and cyclic Adenosine Monophosphate (cAMP)), neuroinflammatory markers (TNF-α, IL-1β, and IL-17), and neurotransmitters (dopamine, norepinephrine, serotonin, GABA, and glutamate) in rats brain (striatum) leads to motor deficits [27].…”
Section: Neurotoxicitymentioning
confidence: 99%